2011
DOI: 10.1111/j.1600-0412.2011.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements as predictors of cephalopelvic disproportion

Abstract: Maternal anthropometric measurements can predict CPD to some extent. Combining maternal measurements with clinical estimates of fetal weight only enhances the predictive value to a relatively modest degree (positive predictive value 24%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 21 publications
9
41
0
Order By: Relevance
“…There were no studies identified examining determinants of caesareans in migrants specifically. However, gestational diabetes mellitus (GDM) and feto-pelvic disproportion are known to complicate delivery and increase the risk of caesarean [104,105] and these are more common in some migrant women [28,39,106]. Reasons for increased risk of GDM in migrants are unknown but might be associated with a genetic pre-disposition, or physiological response to dietary changes; the involvement of a stress response has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…There were no studies identified examining determinants of caesareans in migrants specifically. However, gestational diabetes mellitus (GDM) and feto-pelvic disproportion are known to complicate delivery and increase the risk of caesarean [104,105] and these are more common in some migrant women [28,39,106]. Reasons for increased risk of GDM in migrants are unknown but might be associated with a genetic pre-disposition, or physiological response to dietary changes; the involvement of a stress response has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in other settings have recommended the use of maternal height cut offs of <155.5 cm [20], and <162.5 cm [23] for African mothers. Table 4 shows that increasing the maternal height cut off to the ROC optimum cut off of <160.4 cm improves the sensitivity of the test while increasing the false positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression was used to identify predictors of unfavourable outcomes of labour that included: delivery by cesarean section, vaginal delivery of a baby with an APGAR score of ≤7 at 5 min [19] or mother being referred. To obtain predicted probabilities, all the variables with the optimal cut-off that were significant at the 0.20 level in the univariate analysis were included in the subsequent modeling [20]. To cater for the study design and variability in recruitment numbers from the different sites multilevel logistic regression using the gllamm function in STATA was used to calculate the odds ratios with iterations nipped at 60 for final modeling [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal height correlates positively with her pelvic dimensions and is an important predictor of obstructed labor (Connolly and McKenna, 2001; Kjærgaard et al, 2010; Benjamin et al, 2012). Furthermore, in the “head and trunk skeletal size” PC, trunk breadths feature relatively prominently along with head size.…”
Section: Discussionmentioning
confidence: 99%